Potential Role of Dentin Sialoprotein by Inducing Dental Pulp Mesenchymal Stem Cell Differentiation and Mineralization for Dental Tissue Repair - Zhi Chen; Shuo Chen; Li-An Wu; Guo-Hua Yuan; Guo-Bin Yang (Wolters Kluwer Medknow Publications, 2010)
Introduction: Dentin sialoprotein (DSP) is a dentin extracellular matrix protein, a unique marker of dentinogenesis and plays a vital role in odontoblast differentiation and dentin mineralization. Recently, studies have shown that DSP induces differentiation and mineralization of periodontal ligament stem cells and dental papilla mesenchymal cells in vitro and rescues dentin deficiency and increases enamel mineralization in animal models.The hypothesis: DSP as a nature therapeutic agent stimulates dental tissue repair by inducing endogenous dental pulp mesenchymal stem/progenitor cells into odontoblast-like cells to synthesize and to secrete dentin extracellular matrix forming new tertiary dentin as well as to regenerate a functional dentin-pulp complex. As DSP is a nature protein, and clinical procedure for DSP therapy is easy and simple, application of DSP may provide a new avenue for dentists with additional option for the treatment of substantially damaged vital teeth.Evaluation of the hypothesis: Dental caries is the most common dental disease. Deep caries and pulp exposure have been treated by various restorative materials with limited success. One promising approach is dental pulp stem/progenitor-based therapies to regenerate dentin-pulp complex and restore its functions by DSP induction in vivo.